Evaluation of multi-walled carbon nanotubes performance in adsorption and desorption of hexavalent chromium - Gholipour Mina (Chemical Industry and Chemical Engineering Quarterly, 2012)
In this study, the removal of hexavalent chromium from aqueous solutions using multi-walled carbon nanotubes (MWCNTs) has been investigated as a function of adsorbent dosage, initial Cr(VI) concentration, initial pH, contact time and temperature. Low pH, low initial concentrations of Cr(VI), increasing contact time and high temperature were found as optimal conditions. A comparison of kinetics models applied to the adsorption of Cr(VI) ions on the MWCNTs was evaluated for the pseudo first-order, the pseudo second-order, and Elovich kinetics models, respectively. Pseudo second-order kinetics model was found to correlate the experimental data well. Equilibrium isotherms were measured experimentally and results show that data were fitted well by the BET model. Thermodynamic parameters were estimated and results suggest that the adsorption process is spontaneous, physical and endothermic. The reversibility of Cr(VI) adsorption onto MWCNTs by desorption process and the effect of operating factors such as regeneration solution characteristics, contact time and temperature on this process was investigated. Results show that MWCNTs are effective Cr(VI) adsorbents and can be reused through many cycles of regeneration without any high decreasing in their performance.